2011
DOI: 10.1186/1756-0500-4-116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nail biting and its association with mental health in a community sample of children

Abstract: BackgroundThis study evaluates onychophagia or nail biting (NB) prevalence and association with mental health of a community sample of children from Shiraz, Iran.FindingsThe parents of 743 primary school children, selected by random sampling, reported NB behavior of their children and themselves. Children's mental health problem was assessed using the Strengths and Difficulties Questionnaire (SDQ). 22.3% (95% CI: 19.3 to 25.3) of children had NB behavior in the last three months (girls: 20.1% (95% CI: 15.9 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
3
40
1
7
Order By: Relevance
“…Our recent study (4), in accordance with previous data (5)(6)(7)(8), demonstrated that onychophagia is a frequent problem, affecting about 20-30% of the general population. Onychophagia seems to be rare in children younger than 3-6 years (9, 10), but the frequency increases in children older than 5-6 years, only to decrease again by the age of 18 years.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Our recent study (4), in accordance with previous data (5)(6)(7)(8), demonstrated that onychophagia is a frequent problem, affecting about 20-30% of the general population. Onychophagia seems to be rare in children younger than 3-6 years (9, 10), but the frequency increases in children older than 5-6 years, only to decrease again by the age of 18 years.…”
supporting
confidence: 85%
“…Taking into account that onychophagia may affect up to 30% of the general population (4)(5)(6)(7)(8) it is astounding that this problem is so rarely reported in the literature and has not widely been studied so far. It is worth mentioning that onychophagia cannot be considered as a cosmetic problem or an innocuous behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the highest rate of onychophagia /onychotillomania was found between the ages of 2 and 11 years. Despite the reports in literature stating similar rates for both genders; in our study, rate of them was found to be significantly higher in boys than in girls (17). They should not be considered only as cosmetic problems.…”
Section: Discussioncontrasting
confidence: 89%
“…In the present study, it was observed impact of pacifier sucking habit on OHRQOL, with regard to self image and social interaction. The literature points out that the persistence of these non-nutritive sucking habits, after early childhood, may be a sign of psychological disorders (29) . The significant prevalence of non-nutritive sucking habits in children from 3 to 5 years old was observed, and the pacifier sucking habit was more prevalent than finger sucking.…”
Section: How Often Have You or Another Family Member Because Of Tementioning
confidence: 99%